Determinan Kejadian Anemia Pada Remaja Putri Di SMA Negeri 1 Reteh Kecamatan Reteh Kabupaten Indragiri Hilir Tahun 2019 - Sherly Vermita w; M Dedi Widodo; Leon Candra; Fenti Rialita (Sistem Informasi, 2019)
Anemia is a condition where there is a decrease in the number of red cell mass which is indicated by adecrease in hemoglobin level <11 g / dl, hematocrit, and erythrocyte count (red cell count). The Indragiri HilirDistrict Health Office for girlsin 2016 amounted to 22.8% of 880, 201 young women who experienced anemia.General Objectives Describe and determine Determinants that affect the incidence of anemia in youngwomen in SMA 1 Reteh in 2018. This type of research is observational analytic with Cross Sectional researchdesign. The population in this study were all young female in SMA 1 Reteh with a total of 405 female studentsand the number of samples in this study was 198 students taken using simple random techniques. Theanalysis used was univariate and bivariate analysis with chi-square test. The results showed values forknowledge (P value = 0.001), eating habits for inhibiting iron absorption (P value = 0.001), menstrual patterns(P value = 0.001) and nutritional status (P value = 0.001) meaning that there was a significant relationshipwith the incidence of anemia. It is better for the SMA 1 Reteh to be expected by the teacher to provide anemiaknowledge to the students and put information on anemia. And it is expected that students consumenutritious foods to avoid anemia